Entrepreneurial Behavior in Collectivist Economies: The Roleof Self-Efficacy, ‎Passion, and Agility among Arab Youth - Husain , Dr. Mohammad Khalid; Itani , Dr. Khadija; Dongre , Dr. Sandeep; Winarso , Dr. Eddy; Padhye , Dr. Pradip Sanatkumar; Ak , Dr. Romli S. E. M.; Laheri , Dr. Vishal Kumar; Saeed, Dr. Wizra (International Journal of Accounting and Economics Studies, 2026)
This study explores the psychological and pedagogical drivers of entrepreneurial intention among university students in the United Arab ‎Emirates (UAE), using the Theory of Planned Behavior (TPB; Ajzen, 1991) as its guiding framework. It observes how entrepreneurial self-‎efficacy, passion, agility, and risk propensity influence the formation of entrepreneurial intention and its translation into entrepreneurial ac-‎tion within a collectivist cultural context. A cross-sectional survey of 185 Arab university students was conducted, and data were examined ‎using partial least squares structural equation modeling (PLS-SEM; Hair et al., 2021) via SmartPLS 4.0. The results show that entrepreneur-‎ial self-efficacy, passion, and agility significantly predict entrepreneurial intention. This intention strongly influences entrepreneurial action. ‎However, risk propensity did not show a significant impact, suggesting the presence of culturally specific moderating variables in the ‎UAE’s context, such as familial approval and societal stability. The outcomes offer valuable implications for educators and policymakers ‎aiming to substitute innovation and opportunity recognition through inclusive and context-sensitive entrepreneurship education. This re-‎search contributes to the literature by integrating culturally responsive concepts and reinforcing the alignment between entrepreneurship ‎education and the Sustainable Development Goals (SDGs; United Nations, 2015), particularly SDG 4 (Quality Education) and SDG 8 (De-‎cent Work and Economic Growth), thereby advancing both theoretical and practical understanding of entrepreneurship in developing econ-‎omies.